2009
DOI: 10.1002/pbc.22222
|View full text |Cite
|
Sign up to set email alerts
|

Vaso‐occlusive painful events in sickle cell disease: Impact on child well‐being

Abstract: Background This study describes how painful events affect the health related quality of life (HRQL) of children with sickle cell disease (SCD) and determines the responsiveness of a generic HRQL measure in SCD. Our hypotheses were twofold: 1) HRQL is significantly impaired at presentation to the emergency department for a painful event and 2) PedsQL 4.0 Acute Version Generic Core Scales is responsive to change in the evolution of a painful event. Procedure This prospective cohort study included 57 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 26 publications
5
77
1
3
Order By: Relevance
“…Lowered rates of pain and dactylitis should have a substantial long-term impact with regard to lowering the medical costs of outpatient and inpatient management 14 and improving quality of life. 15 Hydroxyurea was also associated with a 3.5-fold lower rate of ACS and a lower rate of recurrent ACS. A smaller percentage of children in the hydroxyurea group were transfused for ACS compared with the placebo group; however, this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Lowered rates of pain and dactylitis should have a substantial long-term impact with regard to lowering the medical costs of outpatient and inpatient management 14 and improving quality of life. 15 Hydroxyurea was also associated with a 3.5-fold lower rate of ACS and a lower rate of recurrent ACS. A smaller percentage of children in the hydroxyurea group were transfused for ACS compared with the placebo group; however, this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are necessary because of the use of medications, hospitalizations and lost working capacity. Because of these events, there may also be a variable impact on their health-related quality of life (HRQL) (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the reason that two-thirds of 10-16 year-old children with thalassemia did not have any problems with regards to sense of well-being may be this matter. Brandow et al (Brandow, Brousseau, Pajewski, & Panepinto, 2010) performed a study on painful event of blocked arteries in patients with cycle of tuberculosis (a chronic disease) and its effect on the well-being of children. They showed that the mean score of health-related quality of life of children at the time of the painful event was lower than 7 days after it.…”
Section: Discussionmentioning
confidence: 99%